Análise in silico das propriedades farmacológicas e toxicológicas dos organosselênios e ensaios in vitro de atividades antibacteriana e moduladora da resistência a drogas em Staphylococcus aureus - Borges, Nathalie Helen Paes Barreto (2018)
Among several classes of synthetic compounds, organelles have been shown to be important due to the antibacterial effect of different species. The objective of this study was to evaluate a class of organoselenium compounds, derived from selenoglycolic acid, regarding the physical-chemical, toxic, oral bioavailability and permeability characteristics of the blood-brain barrier, as well as interaction with Pglycoprotein and cytochrome P-450 enzymes , performed in silico studies through a free software, Swissadme. In addition, in vitro studies on antibacterial activities, drug resistance modulators and antibiotic synergism were carried out against SA-199B, RN-4220 and IS-58 strains, which are resistant to antibiotics due to overexpression of TetK (tetracycline ), MsrA (macrolides) and NorA (fluoroquinolones and multiple drugs) efflux pumps, respectively. The organoselenium compounds evaluated were generally good candidates for new drugs because they had good cell membrane permeability, good solubility in biological fluids, adequate oral bioavailability, interacted with few cytochrome P-450 isoforms and some organoselenium compounds presented theoretical toxic risk when compared with commercial antibiotics. In addition, HSe-02 and HSe-11 presented theoretical ability to cross a blood-brain barrier, important in the treatment of bacterial meningitis. In the in vitro studies, HSe-01, HSe-06 and HSe-09 showed moderate antibacterial activity, with MIC up to 64 μg/mL in strains that overexpress efflux pumps. In the drug resistance modulation assay, all HSe/Tet combinations reduced tetracycline MIC by up to 256- fold. HSe/Eri combinations also showed promising modulatory activity, with erythromycin MIC reduced by up to 16-fold. The association between organoselenium compounds and ethidium bromide reduced its MIC up to 8-fold, suggesting some kind of interaction, either directly or indirectly with efflux pumps. Several organoselenium compounds were able to reduce the MIC of the NorA pump substrate, berberine, potentializing the effect of this substance. The results presented herein have shown that class of selenoglycolic acid derivatives can be used to potentiate the effect of antimicrobial agents in order to facilitate the reintroduction of currently ineffective antibiotics for the clinical treatment of multiresistant infections.